Patient with cancer of the vulva - case study - Kardyś, Małgorzata; Rożek, Grażyna (Journal of Education, Health and Sport, 2018)
Female genital cancers are a large group among malignancies in the elderly population. The National Program for Counteracting Cancer Diseases for 2016-2020 assumes that the number of cases and deaths of malignant tumors in Poland will increase, and thus it will become an important cause of mortality of population before the age of 65. Among female malignant genital cancers, vulvar cancer is a rare disease. In 2013, vulvar cancer accounted for 2.5-5% of all malignant genital cancers of women. About 500 new cases were reported in Poland every year and about 270 deaths were reported. The aim of the work was to present nursing care for a patient with vulvar cancer. This work uses the case-by-case method. During the implementation of the individual case method, the following research techniques were used: interview, observation, documentation analysis and measurement using selected scales associated with nursing care. The study involved a 76-year-old woman. On the basis of the conducted examinations, it was found that there was a correlation between the severity of pain and the degree of radiation-induced radiation during the sessions of radiotherapy. In addition, the patient's care concerns the scope of self-care and social awareness in the field of interpersonal contacts.Nursing care of a female patient with neoplastic neoplasms should take into account individual nursing with the assumption of a holistic care model. A patient with reproductive organ cancer expects subjective treatment from the family and members of the interdisciplinary team and acceptance of her health problems.